Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Pegawai Di Dinas Pendidikan Kepemudaan Dan Olahraga Kabupaten Karangasem: Penelitian - Ni Kadek Juliantini; Amanda Dewanti (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the effect of work motivation and work discipline on employee performance at the Department of Education, Youth, and Sports of Karangasem Regency. The research problem is motivated by the low level of employee motivation and discipline, which has resulted in suboptimal performance and public services. This study employed a quantitative approach with a causal research design. The population consisted of 50 civil servant employees, all of whom were selected as respondents through a census method. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression. The results indicate that work motivation has a positive and significant effect on employee performance. Work discipline also has a positive and significant effect on employee performance. Simultaneously, work motivation and work discipline have a positive and significant effect on employee performance. The coefficient of determination (R²) of 0.756 indicates that 75.6% of the variation in employee performance can be explained by work motivation and work discipline, while the remaining 24.4% is influenced by other factors outside the study. These findings suggest that improving work motivation and work discipline is an important strategy for enhancing organizational effectiveness and the quality of public services.